Teachers’ Perceptions of the Effects of Differentiated Instruction on Teaching Quality - Niaty Beladinna; Endang Fauziati; Muamaroh (Ilomata International Journal of Social Science, 2026)
This study examines English teachers’ perceptions of the effects of Differentiated Instruction (DI) on teaching quality in English language teaching at MTsN 2 Manggarai Barat, East Nusa Tenggara. This qualitative case study involved three English teachers selected through purposive sampling. Data were collected through questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings indicate that teachers generally hold positive perceptions of DI and consider it supportive of student-centered and inclusive learning practices aligned with the Merdeka Curriculum. However, differences were found in teachers’ understanding of DI, particularly in how instructional differentiation is conceptualized and applied in classroom practice. These findings suggest that while positive perceptions facilitate DI implementation, strengthened conceptual understanding is necessary to ensure consistent instructional quality. The study highlights the importance of targeted professional development to support effective Differentiated Instruction in English language teaching.